Bacterial community composition and function succession under aerobic and anaerobic conditions impacts the biodegradation of 17β-estradiol and its environmental risk. (December 2020) - Zhang, Kun; Zhang, Zhen; Hu, Zheng; Zeng, Feifan; Chen, Chengyu; Yang, Xingjian; Li, Yongtao
Abstract: The widespread detection of 17β-estradiol (E2) in the environment has become an emerging concern worldwide due to its endocrine disrupting effects. This work focuses on the aerobic and anaerobic biodegradations of E2 in various sedimentary environments with different availabilities of electron acceptors, including O2, NO3 −, Fe 3+, SO4 2−, or HCO3 − . The highest removal efficiency (98.9%) and shortest degradation half-life of E2 ( t 1/2  = 5.0 d) were achieved under aerobic condition, followed by nitrate-reducing, ferric-reducing, sulfate-reducing and methanogenic conditions. We propose four different degradation pathways of E2 based on the metabolites identified under various redox conditions. Although most of E2 was effectively removed under aerobic condition, the potential environmental risk still needs to be considered due to the residual estrogenic activity induced by estrone (E1) formation. The endocrine-disrupting activities, as indicated by estradiol equivalent (EEQ) values, were related to E2 degradation rate and metabolite formation. We further analyzed the succession of bacterial community compositions and functions using Illumina HiSeq sequencing and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). The findings herein evidenced that bacterial community compositions and metabolic functions associated with different redox conditions impact the biodegradation of E2 and its endocrine-disrupting activity. This knowledge will be useful in predicting the environmental fates of estrogenic hormones in various sedimentary environments and aid in establishing appropriate strategies for eliminating potential environmental risks. Graphical abstract: Image 1 Highlights: Degradation of E2 under aerobic and anaerobic conditions were systematically studied. We proposed four degradation pathways of E2 based on the identified metabolites. Bacterial structure and function impact degradation of E2 and its environmental risk. Higher persistence of E2 in sedimentary environment explained its frequent detection. Varying species were responsible for E2 degradation under various redox conditions. Abstract : Environmental fates and risks of 17β-estradiol varied with aerobic and anaerobic conditions due to the succession of bacterial community compositions and functions.